Red-light signaling pathway activates desert cyanobacteria to prepare for desiccation tolerance - Hai-Feng Xu; Guo-Zheng Dai; Ren-Han Li; Yang Bai; Ai-Wei Zuo; Lei Zhao; Shu-Ren Cui; Jin-Long Shang; Chao Cheng; Yu-Jie Wang; Gui-Fang Feng; Deqiang Duanmu; et al. (Proceedings of the National Academy of Sciences, 2025)
Desiccation-tolerant cyanobacteria are able to survive frequent cycles of hydration and dehydration, which are closely linked to diurnal light oscillations. Previous studies have shown that light serves as a crucial anticipatory cue, activating desert cyanobacteria to prepare for desiccation. However, the mechanisms underlying their light-coupled desiccation tolerance remain largely unknown. Here, we demonstrate that red-light-induced photosynthetic genes are positively regulated by a LuxR family transcription factor NfSrr1. We further identified the cyanobacteriochrome NfPixJ as interacting with NfSrr1 and functioning as a red light sensor. Phenotypic analysis revealed that the red-light signaling module NfPixJ-NfSrr1 plays a key role in preparing cyanobacteria for desiccation tolerance. This module also regulates the synthesis of protective compatible solutes, suggesting that red light functions as a global regulatory signal for the broader stress response. Phylogenetic analysis indicates that the presence of this red-light signaling pathway, mediated by NfPixJ-NfSrr1 module, correlates with the ability of cyanobacteria to thrive in water-deficit habitats. Overall, our findings uncover a red-light signaling pathway that enhances desiccation tolerance as desert cyanobacteria encounter red light at dawn, before water limitation. These results provide insights into the mechanisms behind light-induced anticipatory stress tolerance in photosynthetic organisms.